Phencyclidine is a negative allosteric modulator of signal transduction at two subclasses of excitatory amino acid receptors. - Wroblewski, J T (1987)
Phencyclidine (PCP) and some of its pharmacological congeners inhibit the signal transduction at specific excitatory amino acid receptors of cerebellar granule cells in primary cultures. These drugs do not bind to the transmitter recognition sites, and affinity of this specific binding site is increased by the presence of the transmitter bound to its recognition sites. PCP inhibits phosphatidylinositol phosphate hydrolysis mediated by Mg2+-sensitive glutamate receptors (GP1) but not that mediated by Mg2+-insensitive glutamate receptors (GP2). In addition, PCP inhibits Ca2+ influx and cGMP formation mediated by the activation of Mg2+-sensitive glutamate receptors (GC1) but not that mediated by Mg2+-insensitive glutamate receptors (GC2). In this cell culture the activation of phosphatidylinositol phosphate hydrolysis by muscarinic receptor agonists is not affected by PCP. Since PCP inhibits noncompetitively GP1 and GC1 signal transduction it may act as a negative allosteric modulator of signal transduction at both receptors. The pharmacological profile of PCP and its congeners delimits a class of drugs modulating allosterically the action of the primary transmitter at GP1 and GC1 receptors. These drugs need the presence of the transmitter to act and they cannot be termed inverse agonists because they are devoid of activity in the absence of the transmitter; moreover, they do not bind to the transmitter recognition site nor do they prevent the transmitter binding to its recognition sites.